FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEREMPUAN MEMILIH BERWIRAUSAHA (Studi Kasus Pada Penjahit Pakaian di Kecamatan Tampan - Pekanbaru) - Sehani Sehani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2010)
The entrepreneurship is one the Indonesian economy driving factors. It is not only conducted by the men, women too. Some of them make this entrepreneurial activity as a livelihood, and some are making it as a sideline. The results of 37 women who work as taylor in Tampan, Pekanbaru district showed that the factor of independence, emotional and educational together have a significant influence on the women decision to choose entrepreneurship. Partially proved that the independence of the variables have a dominant influence on the women decisions to choose entrepreneurship as a profession.